2008
DOI: 10.1002/num.20373
|View full text |Cite
|
Sign up to set email alerts
|

An approximation to the solution of telegraph equation by variational iteration method

Abstract: The variational iteration method (VIM) has been applied to solve many functional equations. In this article, this method is applied to obtain an approximate solution for the Telegraph equation. Some examples are presented to show the ability of the proposed method. The results of applying VIM are exactly the same as those obtained by Adomian decomposition method. It seems less computation is needed in proposed method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 4 publications
0
31
0
Order By: Relevance
“…It has been shown that the VIM is an efficient algorithm for solving integro‐differential equation (see for example [29–31]). In [32], Biazar et al applied the VIM to the telegraph equation with some initial conditions. A lot of papers have been written concerning the VIM and we have reviewed only a few of them.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the VIM is an efficient algorithm for solving integro‐differential equation (see for example [29–31]). In [32], Biazar et al applied the VIM to the telegraph equation with some initial conditions. A lot of papers have been written concerning the VIM and we have reviewed only a few of them.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed method gives not only the function v but also its derivative, simultaneously. As Biazar et al mentioned in [32] and we have observed in this article, the solution procedure is very simple by means of variational theory, and only a few steps lead to high accurate solution valid for the whole solution domain. The method does not need small parameter or linearization.…”
Section: Discussionmentioning
confidence: 78%
“…It has been shown that the VIM is an efficient algorithm for solving integro-differential equation (see for example [29][30][31]). In [32], Biazar et al applied the VIM to the telegraph equation with some initial conditions. A lot of papers have been written concerning the VIM and we have reviewed only a few of them.…”
Section: S(x)dx = Q (0)mentioning
confidence: 99%
“…This is the main advantage of fractional derivatives in comparison with classic integral-order models, in which such effects are in fact neglected. Some scholars have been interested in research on the problems involving the fractional order partial differential PDEs [1,[4][5][6][8][9][10]15,16]. The numerical modeling and simulation for fractional calculus have been stimulated due to their numerous applications in physics, fluid mechanics, biology, and engineering.…”
Section: Introductionmentioning
confidence: 99%